Diversidad genética de Mycoplasma hyopneumoniae en granjas porcinas de Argentina - Tamiozzo, P.J. (2011)
Mycoplasma hyopneumoniae is the etiological agent of porcine enzootic pneumonia (EP), one of the respiratory diseases with higher impact on the swine industry. Knowledge of M. hyopneumoniae genetic diversity is useful for epidemiological and pathogenesis studies to develop effective control strategies. In this work, 39 DNA samples from nasal swabs and bronchial lavages, that previously rendered positive for this pathogen by nPCR, were analyzed. They corresponded to pigs of different ages, belonging to seven farms. For M. hyopneumoniae typing using DNA from nasal swabs, a nPCR assay was developed to amplify the region coding for the serine tandem repeat domain of p146 gene. For samples from bronchial lavages, the same region was amplifi ed by PCR, along with other VNTRs (variable number tandem repeats) from other loci. With this approach, that proved to be useful for the direct analysis of clinical samples without prior isolation of the pathogen, the genetic diversity of M. hyopneumoniae strains circulating in our country could be evidenced. Different genotypes were\nfound among farms and also among animals from a same farm, but there were also animals (from a different or a same farm) that harbored a same M. hyopneumoniae genotype.